Formulation of a tropical beverage by applying heat treatment and high hydrostatic pressure - Marengo-Orozco, Carla (Array, 2020)
Research background. Passion fruit and carrot have a good antioxidant capacity; however, their consumption is low. There is no information on their use in beverages or in processes such as high hydrostatic pressure, which provides the safety of the drink without affecting its quality. Experimental approach. In this study the effect of high hydrostatic pressure (HHP; 500 MPa for 250 s at 25 °C) and thermal processing (at 65 °C for 10 min, 75 °C for 2 min and 95 °C for 1 min) were evaluated in the formulation of a cold-pressed beverage from purple passion fruit, green passion fruit and carrot juice, taking into account antioxidant capacity, vitamin C concentration, sensorial evaluation and microbiological growth at 8 °C. Results and conclusions. The formulation containing 67 % purple passion fruit, 17 % green passion fruit and 17 % carrot was the one that stood out with its antioxidant capacity, high vitamin C concentration and sensorial evaluation. The HHP treatment preserved the antioxidant capacity and vitamin C concentration, and resulted in the best scent. Juices stored at 8 °C did not show microbial growth. Novelty and scientific contribution. In this study, we used tropical raw materials with good sensory acceptance and antioxidant capacity that could be used in the production of high value-added foods. Additionally, the research demonstrated that HHP is a conservation method that maintains the antioxidant capacity, vitamin C and aroma of the beverage to a greater extent than thermal treatments; the latter is of interest for its use in minimally processed products and functional food.